#1**0 **

*f(x)=(16*64)^0+64^2/3

-Distribute the 0

*f(x)= (16*0)+(64*0)+64^2/3

-making f(x)=64^2/3

*f(x)=0+64^2/3

-when you are going to enter powers that are fractions in the calculators make sure to use Parenthesis "()"

*f(x)=64^(2/3)

-multiply 64 and it's power = 64^(2/3) = 16, so f(x) aka y=16

-Distribute the 0

*f(x)= (16*0)+(64*0)+64^2/3

-making f(x)=64^2/3

*f(x)=0+64^2/3

-when you are going to enter powers that are fractions in the calculators make sure to use Parenthesis "()"

*f(x)=64^(2/3)

-multiply 64 and it's power = 64^(2/3) = 16, so f(x) aka y=16

Guest Feb 1, 2012